1996
DOI: 10.1044/jshr.3905.1034
|View full text |Cite
|
Sign up to set email alerts
|

Does Speech Emerge From Earlier Appearing Oral Motor Behaviors?

Abstract: This investigation was designed to quantify the coordinative organization of mandibular muscles in toddlers during speech and nonspeech behaviors. Seven 15-month-olds were observed during spontaneous production of chewing, sucking, babbling, and speech. Comparison of mandibular coordination across these behaviors revealed that, even for children in the earliest stages of true word production, coordination was quite different from that observed for other behaviors. Production of true words was predominantly cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
114
1
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(147 citation statements)
references
References 36 publications
30
114
1
2
Order By: Relevance
“…Previous studies of the link between oral motor skills and language have tended to look at simple movements more closely resembling eating movements (Moore & Ruark, 1996), or fast repeated movements (Dworkin & Culatta, 1985), neither of which seem to have a relationship with language development and disorders in these two studies. Our data suggest that more difficult oral movements are more closely related to language skills, possibly because they are more speech-like.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of the link between oral motor skills and language have tended to look at simple movements more closely resembling eating movements (Moore & Ruark, 1996), or fast repeated movements (Dworkin & Culatta, 1985), neither of which seem to have a relationship with language development and disorders in these two studies. Our data suggest that more difficult oral movements are more closely related to language skills, possibly because they are more speech-like.…”
Section: Discussionmentioning
confidence: 99%
“…There is in fact very little data on this link. Moore and Ruark (Moore & Ruark, 1996) used EMG recordings to examine the coordination of activity in feeding behaviour and speech motor behaviour, and suggested that these were not linked. However, the types of motor activity examined in the non-speech category in this study were mainly those involving a single set of muscles -opening and closing the mouth, chewing etc.…”
Section: Introductionmentioning
confidence: 99%
“…This concern was addressed in several ways in this study, which is one of a series of investigations of these children (e.g., Moore and Ruark 1996). First, the distance between electrode pairs was large compared with distance within electrode pairs (e.g., 0.5-cm interelectrode distance for ABD electrode pairs, which were ~5 cm from the nearest masseter pair) somewhat reducing volume conduction effects.…”
Section: Electromyography and Data Recordingmentioning
confidence: 99%
“…There has been, however, a trend since the mid-1990s toward certain claims about the neurodevelopmental substrates of speech-sound disorders. Notably in the USA, for example, some speech treatment has been based on the hypothesis that some children have significant deficits in variables such as 'oral sensation', 'oral-motor development', 'sensory-motor integration' and other currently unsupported explanatory constructs (see evaluative reviews by Moore and Ruark, 1996;Weismer, 1997;Forrest, 2002;Strand, Hodge and Forrest, 2002). We, too, suggest that such etiological claims lack the research support needed to recommend oral-motor therapy as a necessary or sufficient treatment component for children with common speech delay.…”
mentioning
confidence: 99%